FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN ORANG TUA BAYI BBLR DI RSUD HM RYACUDU DAN RS HANDAYANI KOTABUMI – LAMPUNG UTARA - Mutiara, Siti; Hastuti, Retno Puji (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2016)
Low Birth Weight (LBW) infants require intensive care in hospital until the baby is stable and ready to get home care. Health problems and management in hospitals cause anxiety in the parents. This research is an analytic research with cross sectional design to determine factors related to the level of anxiety of parents of LBW infants are implemented in hospitals HM. Ryacudu and RS Handayani Kotabumi on 3 trdJune until5trd July 2015. The population are parents LBW infants treated in Perinatologis HM. RyacuduHospitals and Handayani Hospitals with a large sample of 30 people who obtained using techniques Concecutive sampling. Collecting data by questionnaires and measurement of anxiety level using the Hamilton Anxiety Rating Scale (Hars). Univariate data analysis with frequency distribution and bivariate using Chi Square test. The results showed the majority of parents LBW infants aged young adults (76.6%), female (60%), less educated (80%) and a moderate – Weight level of anxiety- (70%). There was no significant relationship between age (p = 0073) and gender (p = 0745) with the level of anxiety of parents LBW infants, but education was significant with pvalue = 0.001 (p-value> 0:05). Suggestions of research that HM Ryacudu and Handayani’s Hospitals can provided care that focuses on family (family centered care) include: bring of information, kangoroo Mother Care, therapeutic communication and stress management to reduce anxietylevel of parents LBW infants, especially in young mothers and less educated.